Counterfactuality of the Ethical Norms of Higher Education - Natalia Boychenko (International Society of Philosophy and Cosmology, 2017)
Usage of the counterfactuality as a term for marking the modality to some event becomes a new trend in social sciences. Recently this term was popular almost exclusively in psychology - especially in study of cognitive processes, but now it receive wide spectrum of interpretations: from economic to philosophical one. Most of such interpretations is concentrated near the problem of somebody's attitude to situation that he or she was involved in. Meanwhile the term "counterfactuality" marks the real influence of the person on the course of events rather than his or her pure mental states. The person could change the future events due to his or her activity about these events: these changes rarely could be exactly the same that were calculated, desirable or even acceptable for this person, but these changes are for sure the consequence of his or her decision - direct or indirect, substantial or accidental, necessary or extraneous, evidently relevant or seemingly unrelated. For the philosophy the situation with ethical optation and its consequences is significant. Typical for analytic philosophy is the reconstruction of positivist logic of counterfactuality as possibility. According to this positivist point of view, we should not accept any human discovery, any creation because of their improbability - the sentences about them were simply the consequences of false sentences. More important is the fact that the consequents of the counterfactual conditional judgments are always true. Nobody can take the antecedent of the counterfactual conditional judgments as false from the point of view of human will, i.e. from the point of view of our intention and results of its implementation in our activity and our creations. These consequences are real because men act according to their definition of situation: their belief motivates them and push them to make real things that were unreal before. Reality of mind becomes real materially due to human activity. This is the way of design of future human nature on the basis of future human image